Sexual consent education among youth experiencing homeless in Toronto, Canada: findings from an arts-based and qualitative study - Lesley Gittings; Carmen H. Logie; Miriam Selick; Ayla Lefkowitz (Wellbeing, Space and Society)
Homeless youth face elevated risks of sexual violence, diminishing their access to sexual-well-being, justice and health. Sexual consent—expressed agreement, capacity and freedom to participate in sexual practices—is fundamental to realising sexual well-being, yet is underexplored with this population. Arts-based approaches are promising for advancing health and well-being, yet gaps exist regarding their role in sexual consent education with homeless youth. This study explores homeless youth experiences of sexual consent and violence, and the potential of arts-based approaches in sexual consent education. We conducted online focus groups and in-depth interviews (2021–2022) with youth who have experienced homelessness, and key informant (KI) interviews with youth workers in Toronto. We explored: a) understandings of sexual consent, b) needs and challenges in sexual consent education, and c) two arts-based sexual consent education approaches (poetry and comics). Data were transcribed verbatim and analysed thematically, informed by the social contextual framework which attends to relational, material, and symbolic contexts. Participants (N = 24) included 17 youth aged 18–29 with homelessness experiences (4 FGs; 5 interviews; mean age 22.57, SD 3.22), and 7 KI (1 FG; 5 interviews; mean age 27.25, SD 5.54). Factors shaping exposure to sexual violence victimization included: relational (in-person and digital sexual spaces, lack of social support), material (insecure housing, poverty) and symbolic (gender, sexual orientation, substance use stigmas) contexts. These create environments where homeless youth experience diminished sexual self-determination, security and safety. Poetry and comics are effective and acceptable when tailored to the realities of homeless youth, and focused on empowerment rather than only technical skills.